The Comprehensive Morphological Criteria for the Diagnosis of Subclinical Bacterial Maternal-Fetal Infection in Offspring - Talapova, Polina; Sorokіna, Iryna; Markovskyi, Volodymyr; Tovazhnianska, Vira; Sakal, Anna; Zvierieva, Iryna (My University, 2021)
The paper presents study materials devoted to determining the morphofunctional state of progeny’s organs developed under subclinical bacterial maternal-fetal infection (MFI) in order to define the comprehensive diagnostic criteria of this pathology. The rat models of subclinical MFI caused separately by E. coli, S. aureus, and K. pneumoniae were used, the set of diagnostic tools (histopathological staining of paraffin sections of aorta (AO), pulmonary artery (PA), thyroid (TG), and adrenal glands (AG), liver (LV) of fetuses with H&E, Mallory’s trichrome and Van Gieson's methods, optical microscopy, morphometry, and immunofluorescence with the use of ImageJ software) was applied. Statistical analysis was performed in Microsoft Excel 365 and R. Depending on the organ, the null hypothesis was rejected when p<0.05 or p<0.001. The assemblage of statistically significant diagnostic parameters of the subclinical MFI damaging effect in offspring’s organism was determined: for AO and PA – endotheliocyte’s height, the optical density of fluorescence (ODF) of CD34-positive cells, type III and IV collagens; for TG – thyrocyte’s height, nuclear-cytoplasmic ratio (NCR), follicle’s square, T4 OD; for AG – adrenocorticocytes’ density in zona glomerulosa, adrenocorticocyte’s NCR, cortisol ODF in zona fasciculata; for LV - hepatocytes’ density, NCR, the absolute number of IL-6 producing cells. Conclusion: in this study, we have proved the presence of pathomorphological substrate and defined dynamics of morphofunctional changes forming in the fetal organism under the bacterial MFI that enables the use of obtained values as diagnostic criteria of this pathology.
Keywords: infectious disease transmission; fetus; pregnancy complications; infectious; morphological and microscopic findings; Escherichia coli; Staphylococcus aureus; Klebsiella pneumoniae